Combustion adjustment test of circulating fluidized bed boiler. (September 2017) - Qi, Guoli; Zhang, Songsong; Liu, Xuemin; Guan, Jian; Chang, Yongqiang; Wang, Zhongwei
Abstract: To achieve optimal operation, a combustion adjustment test were carried out in a 240 t/h CFB boiler. Three factors, including bed pressure drop, primary air flow and secondary air flow were studied, each of which had three values of factor levels. Results show that the sensible heat loss in exhaust flue gas is the largest part of heat loss, accounting for more than 75%. To achieve higher thermal efficiency, the bed pressure drop should be maintained around 7.2 kPa, the oxygen content in flue gas around 5%, and the bed temperature around 900 °C. From the point of combustion efficiency, the boiler can be operated under a relatively low bed pressure drop, around 6.7 kPa. The heat losses due to the unburned combustibles are relatively small. The NO x concentration in flue gas was also studied, from which it can be concluded that the emissions targets should be set up in combination with the boiler efficiency, especially CO concentration in flue gas. Through combustion adjustments, the NO x emission can be decreased by about 50% without affecting the boiler efficiency.